(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2017)
This article presents the results of a project implemented in the Spanish teacher training program of the Universidad CatÃ³licaÂ Silva HenrÃquez (UCHS). The objective of the investigation was to contribute to the development of disciplinar competences related to text production in first year students from the Oral and Written Expression course. Based on the concept of academic literacy, this was an action-research, which results show the impact of working on mentioned competences with peer-tutors, allowing students to advance significantly in terms of discourse competence and in the courseâ€™s overall performance.